Overview of Cellular Transplantation in Diabetes Mellitus: Focus on the Metabolic Outcome. (10th February 2015) - Luzi, Livio; Benedini, Stefano; Caumo, Andrea; Terruzzi, Ileana
Abstract : Diabetes mellitus is a metabolic disease possible to treat via several different therapeutic approaches. Since the advent of insulin in 1922, type 1 diabetes mellitus has become a chronic treatable disease. Nonetheless, type 1 diabetes mellitus can be a devastating disease when the macro- and microangiopathic complications take place after several years of illness. Starting from the eighties, pancreas/islet transplantation has become a potential innovative treatment of diabetes mellitus. The major advantage of pancreas/islet transplantation is the restoration of c-peptide cosecretion along with insulin; the major disadvantage is the need to administer immunosuppressive drugs which are diabetogenic themselves. Islet transplantation is the progenitor of more recent forms of cellular and stem cell therapies which will be reviewed herein. Cellular therapies for diabetes mellitus are still an experimental procedure. Herein we present the actual current achievements and an outlook of close future possible advancements in the area of cellular transplantation for the cure of diabetes mellitus.